Culturally appropriate care to support maternal positions during the second stage of labour: Midwives' perspectives in South Africa - Maurine R. Musie; Mmapheko D. Peu; Varshika Bhana-Pema (AOSIS, 2022)
Background: 'Doing what the Romans do in Rome' was an expression raised by one of the midwives following workplace culture and disregarding women's birth choices. Midwifery practice in South Africa caters for a culturally diverse ethnic groups of childbearing women. Culturally appropriate care highlights the importance of including women in decision-making concerning their birth preferences including maternal positions during labour. Women's right to choose their maternal position and cultural preferences during labour has been overlooked, leading to poor maternal healthcare provision and negative birth experiences. Aim: In this article, the researchers aimed to describe and explore midwives' perspectives on culturally appropriate care to support maternal positions during the second stage of labour. Setting: Midwives working in the maternity ward in a public hospital in South Africa. Methods: A qualitative descriptive design using individual interviews was used to collect data. The participants were selected using the purposive sampling method. The study population comprised 20 midwives who volunteered to participate in the study. Data were transcribed manually and analysed using thematic analysis. Results: The four main themes are as follows: (1) Caring for women from various ethnic groups, (2) midwives disregard women's beliefs and culture, (3) midwife personal cultural attributes and (4) midwifery unit workplace culture. Conclusion: The authors concluded that culturally appropriate care towards the women's choices of birth position during the second stage of labour should form an integral part of the midwifery care rendered.